Rethinking ecosystem service indicators for their application to intermittent rivers - Pastor, A.V. (2022)
In these times of strong pressure on aquatic ecosystems and water resources due to climate change and water abstraction, intermittent rivers and ephemeral streams (IRES) (rivers that periodically cease to flow and/or dry) have become valuable assets. Indeed, not only do they supply water but they also offer services for humanity. Despite a growing recognition towards IRES, information for assessing their ecosystem services (ES) remains scarce. In a first step, an international interdisciplinary group of researchers developed a methodological framework to acknowledge ES provided by IRES using 109 indicators. A subset of selected ES indicators was then applied to two case studies: the Rio Seco in the Algarve (Portugal) and the Giofyros River in Crete (Greece). This paper discusses the applicability of these indicators, including the temporal and spatial variability of IRES flow regimes. Aspects of the framework, such as the methods and time required for data collection, the nature (demand or supply) and functionality of each indicator are discussed. The new framework accounts for flowintermittence in ES analyses and can help scientists and water managers to i) increase the ease and justification for IRES use in management approaches and ii) improve their conservation and restoration with a comprehensive set of appropriate indicators for IRES. In addition, the comprehensive nature of the proposed indicators ensures that they can be understood by a broad audience and easily applicable. Since they were designed through a public participation process, the setting has been prepared for holistic stakeholder analysis and education around IRES functions and associated ES. From a management point of view, it would be particularly relevant to perform an economic evaluation with this new framework to understand the value of each ES category and their tradeoffs. For the scientific community, however, it is important to consider public preferences to design socially accepted policies. The proposed indicators can successfully bridge these elements, hereby establishing a solid basis for the assessment of ES provided by IRES.